2008
DOI: 10.3184/030823408x340771
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 14-aryl-14H-dibenzo[a,j]xanthene Derivatives Catalysed by Expanded Graphite under Solvent-Free Condition

Abstract: A convenient eco-friendly procedure has been developed for the synthesis of 14-aryl-14H-dibenzo [a,j]xanthene derivatives by one-pot condensation of 2-naphthol and aryl aldehydes catalysed by expanded graphite under solventfree conditions. The present methodology offers several advantages such as excellent yields, shorter reaction times, low cost and reusability of the catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Meanwhile, the increase of the solubility of carbon dioxide in solution also enhances the requisite supersaturation to nucleate of the intermediate basic cupric carbonate. The rate of nucleation is speeded up and this helps to receive much uniform and small basic cupric carbonate [12]. The subsequent decomposition of basic cupric carbonate consequently produces fine grained CuO clusters in nanometer size as well as even distribution on the surfaces of the molecular sieves.…”
Section: Advanced Materials Research Vols 284-286mentioning
confidence: 99%
“…Meanwhile, the increase of the solubility of carbon dioxide in solution also enhances the requisite supersaturation to nucleate of the intermediate basic cupric carbonate. The rate of nucleation is speeded up and this helps to receive much uniform and small basic cupric carbonate [12]. The subsequent decomposition of basic cupric carbonate consequently produces fine grained CuO clusters in nanometer size as well as even distribution on the surfaces of the molecular sieves.…”
Section: Advanced Materials Research Vols 284-286mentioning
confidence: 99%
“…[ 1 ] Xanthenes, benzoxanthenes, coumarin, and fused coumarins are privileged categories of this class of compounds. [ 2,3 ] Xanthenes and benzoxanthenes were reported to exhibit an extensive range of biological and pharmaceutical properties, [ 4–6 ] including their use as cytotoxic agents [ 7 ] and as antagonists to inhibit zoxalamine activity. [ 8 ] They were also reported to have anti‐inflammatory, [ 9 ] antiviral, [ 10 ] and bactericidal activities.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to a helpful review of literature in this publication, Singh and coworkers 1 developed an eco-friendly solventfree condensation method to obtain 14-aryl-or alkyl-14H-dibenzo [a, j] xanthenes using P2O5 or InCl3 as catalysts. For the synthesis of 14-aryl-14H-dibenzo [a, j] xanthene derivatives, Geng-Chen Li, has used aryl aldehydes, and freshly prepared expanded graphite as a catalyst 10 , while Hamid Reza Shaterian et al, reported the use of ferric hydrogen sulfate and aluminum hydrogen sulfate as catalysts 11,12 . Carbon tetra bromide (CBr4) 13 , and polyvinyl poly pyrrolidine-supported boron trifluoride (PVPP-BF3) 14 were the other important catalysts used for the synthesis of dibenzo xanthenes.…”
Section: Introductionmentioning
confidence: 99%